Increasing Improvements to the Production Process to Realizing Halal Culinary in Tourist Village - Dede R. Oktini; Nurdin, Nurdin; Allya Roosalyn; Maharani, Nina (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
This activity will be directed at meatball businesses in Rende. This activity is carried out to assist businesmen in making improvements production process, procuring materials, namely purchasing meat which must be purchased from butchers who have a halal certificate. The process of making meatballs must also be done in a clean place, clean equipment, clean hands and body, enough water, using special gloves. This activity method consists of several stages, namely a workshop where the trainer already has a certificate accompanying halal products. The second stage is assistance in improving the production process. The third stage is assistance in making the NIB. If the business actor already has an NIB, the next stage is to apply for a halal certificate. The results of this activity only produced 3 NIB due to technical problems with the application and cellphone numbers that could not be followed up.